Strategic Approach for Enhancing Sensitivity of Ammonia Gas Detection: Molecular Design Rule and Morphology Optimization for Stable Radical Anion Formation of Rylene Diimide Semiconductors - Oh, Byeong M.; Park, Sung Ha; Lee, Jeong Hyeon; Kim, Jin Chul; Lee, Jong Bum; Eun, Hyeong Ju; Lee, Yun Sang; Seo, Bo Eun; Yoon, Woojin; Kwon, Ji Eon; Yun, Hoseop; Kwak, Sang Kyu; et al. (Advanced Functional Materials, 2021)
Herein, a strategic approach to enhance the sensitivity of ammonia gas detection using organic semiconductors by boosting the efficiency of ammonia gas-induced stable radical anion formation (SRAF) is reported. This is achieved through rational molecular design and engineering of field-effect transistors (FETs). New rylene diimide derivatives are designed and used to prepare molecular templates for efficient SRAF in thin films, and they are applied as gas-adsorbing active layers in FETs. Substituting linear-shaped perfluoroalkyl (PF) groups to π-electron-deficient naphthalene diimide (NDI) backbone enhances the ammonia gas detection limit to 200 ppb, attributed to the strong electron-withdrawing capability and low steric hindrance of PF groups. Replacing the core backbone (NDI) with perylene diimide (PDI) while retaining the PF group further enhances gas-responsivity up to 18.17 (1700% increase in current) due to the enlarged π-conjugated bridge area. Computational characterization further supports that high electron affinity of the PDI-PF molecules and a larger gas-adsorption area in the PDI core result in the exceptional ammonia gas sensitivity. In addition, beneficial molecular orientation and nanopore formation of PDI-PF facilitate gas adsorption, resulting in remarkably enhanced gas-responsivity. The results indicate that molecular engineering for high-efficiency SRAF suggests a new strategy for developing high-sensitivity ammonia sensing platforms.
Keywords: Electronwithdrawing; Field effect transistor (FETs); High electron affinities; Molecular engineering; Molecular template; Nanopore formation; Naphthalene diimide; Strategic approaches; electron-withdrawing groups; gas responsivity; gas sensors; organic field-effect transistors; stable radical anion formation